2010
DOI: 10.1371/journal.pone.0010124
|View full text |Cite
|
Sign up to set email alerts
|

MVL-PLA2, a Snake Venom Phospholipase A2, Inhibits Angiogenesis through an Increase in Microtubule Dynamics and Disorganization of Focal Adhesions

Abstract: Integrins are essential protagonists of the complex multi-step process of angiogenesis that has now become a major target for the development of anticancer therapies. We recently reported and characterized that MVL-PLA2, a novel phospholipase A2 from Macrovipera lebetina venom, exhibited anti-integrin activity. In this study, we show that MVL-PLA2 also displays potent anti-angiogenic properties. This phospholipase A2 inhibited adhesion and migration of human microvascular-endothelial cells (HMEC-1) in a dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 46 publications
0
38
0
5
Order By: Relevance
“…The vinblastine-induced collapse required Rho GTPases and was blocked with C3 exoenzyme and dominant negative forms of RhoA and RhoC, indicating microtubule depolymerization induced Rho GTPase activation and collapse of endothelial networks [153] . In separate studies, Luis and colleagues [173] recently reported that MVL-PLA2, a phospholipase A2 from snake venom, increased microtubule dynamics and blocked angiogenesis. MVL-PLA2 likewise disrupted focal adhesions, contributing to failed angiogenic responses [173] .…”
Section: Cross-talk Between Microtubules and Actinmentioning
confidence: 99%
See 1 more Smart Citation
“…The vinblastine-induced collapse required Rho GTPases and was blocked with C3 exoenzyme and dominant negative forms of RhoA and RhoC, indicating microtubule depolymerization induced Rho GTPase activation and collapse of endothelial networks [153] . In separate studies, Luis and colleagues [173] recently reported that MVL-PLA2, a phospholipase A2 from snake venom, increased microtubule dynamics and blocked angiogenesis. MVL-PLA2 likewise disrupted focal adhesions, contributing to failed angiogenic responses [173] .…”
Section: Cross-talk Between Microtubules and Actinmentioning
confidence: 99%
“…In separate studies, Luis and colleagues [173] recently reported that MVL-PLA2, a phospholipase A2 from snake venom, increased microtubule dynamics and blocked angiogenesis. MVL-PLA2 likewise disrupted focal adhesions, contributing to failed angiogenic responses [173] . In line with this observation, TAE226 inhibition of focal adhesion kinase blocked tube formation in vitro and microvessel density in subcutaneous tumors [174] .…”
Section: Cross-talk Between Microtubules and Actinmentioning
confidence: 99%
“…In vitro , the svPLA 2 s can also modulate cell adhesion and cell proliferation and have anti-angiogenic properties [9,10,11]. Furthermore, a number of studies describe the anti-microbial properties of several svPLA 2 s against Gram negative [12] and Gram positive bacteria [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we did not observe a measurable growth rate increase in growth factor-induced protrusions in epithelial cells that appear morphologically quite similar to endothelial cells migrating along tension tracks 25 . In this regard it is interesting to note that low doses of microtubule perturbing drugs increase microtubule dynamics in endothelial cells, 21 , 22 , 26 an effect that also is unique to endothelial cells. Together, these observations suggest endothelial cell-specific mechanisms of microtubule regulation, and it will be interesting to see whether this can be therapeutically exploited.…”
Section: Resultsmentioning
confidence: 61%